THE EFFECTIVENESS OF STEM CELL SECRETOME ON POST-TOOTH EXTRACTION WOUND HEALING - Depi Lusianti; Wasis Syahwanda (Journal of Stem Cell Research and Tissue Engineering, 2026)
Tooth extraction is a common surgical procedure performed in dental practice and may cause damage to both soft tissue and alveolar bone. The post-tooth extraction wound healing process involves various biological mechanisms, including inflammation, cell proliferation, angiogenesis, and tissue remodeling. In recent years, stem cell secretome has emerged as a promising regenerative therapy approach because it contains various bioactive factors such as growth factors, cytokines, and extracellular vesicles that play important roles in tissue repair. This study aimed to evaluate the effectiveness of stem cell secretome on post-tooth extraction wound healing through a systematic review method. Literature searching was conducted using the PubMed, Google Scholar, and ScienceDirect databases within the 2020–2026 publication period. Articles were selected based on inclusion and exclusion criteria according to the PRISMA guidelines. The review results showed that stem cell secretome was able to enhance fibroblast proliferation, angiogenesis, collagen deposition, wound epithelialization, and alveolar bone regeneration. In addition, secretome also played a role in reducing inflammatory responses, thereby accelerating the oral wound healing process. Based on the results of this systematic review, stem cell secretome has effective potential as a regenerative therapy to accelerate post-tooth extraction wound healing. However, further clinical studies are still needed to confirm its effectiveness and safety in humans.